Nature of science, scientific and geoscience models: Examining students and teachers’ views - Torres, Joana; Moutınho, Sara; Vasconcelos, Clara (Journal of Turkish Science Education, 2015)
This study investigates Portuguese science teachers’ and Portuguese high school students’ views regarding nature of science, scientific models and Geoscience models and explores the relations between their views. It also examines how Portuguese science teachers value and use models in science classroom. A survey was applied to 145 science teachers and 415 students of the last year of secondary school, who answered to 14 multiple choice questions. Descriptive analyses showed that teachers and students hold intermediate views regarding nature of science and scientific models. Some errors were also detected concerning Geoscience models. T-test analyses showed significant differences between teachers and students’ views, as teachers gave globally more informed answers. Authors considered that more attention should be given to teachers training regarding those issues and that more research is needed in order to understand how teachers deal with nature of science teaching and how they value and use models in classes.